The Relationship Between Emotional Intelligence Level and Conflict Management Strategies for Female Practicing Nurses with Dual Roles in the Inpatient Room of RSUD Sumedang - Ana Fitrianingsih; Heri Ridwan; Iyos Sutresna (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
The nursing environment is unique and has the potential for conflicts to arise. Effective conflict management is crucial for redirecting disputes in a constructive direction. Emotional intelligence , as an internal personality characteristic, significantly influences conflict management. This research aims to determine the relationship between emotional intelligence  and conflict management strategies. A quantitative methodology was employed, utilizing Spearman Rho correlation analysis to analyze the data. The sample in this study consisted of 107 female practicing nurses with multiple roles in the inpatient ward of RSUD Sumedang, selected using the proportional random sampling technique. The alternative hypothesis (Ha) is accepted, indicating a significant relationship between the level of emotional intelligence  and the conflict management strategies of competing, collaborating, compromising, avoiding, and accommodating, with significance levels and correlation coefficients, namely <.001 (-0.510), <.001 (0.614), 0.038 (0.201), <.001 (-0.757), and <.001 (0.688), respectively. Based on these results, it can be concluded that the level of emotional intelligence  is positively correlated with conflict management strategies such as collaborating, compromising, and accommodating. Meanwhile, conflict management strategies involving avoiding and competing show a negative correlation. This demonstrates that selecting a constructive conflict management strategy requires a high level of emotional intelligence . Conversely, nurses possessing elevated emotional intelligence  may lean towards avoiding or refraining from aggressive competition in conflict situations to preserve positive relationships among colleagues. Hence, there is a need for comprehensive development of emotional intelligence  and conflict management training.